Activity of tyrosol against single and mixed-species oral biofilms - Arias, L. S. [UNESP]; Delbem, A. C.B. [UNESP]; Fernandes, R. A. [UNESP]; Barbosa, D. B. [UNESP]; Monteiro, D. R. [UNESP] (Oxford University Press (OUP), 2016)
Aim: This study aimed to evaluate the effect of tyrosol on the formation of single and mixed biofilms of Candida albicans ATCC 10231, Candida glabrata ATCC 90030 and Streptococcus mutans ATCC 25175 formed on acrylic resin (AR) and hydroxyapatite (HA) surfaces. Methods and Results: Single and mixed biofilms were formed on AR and HA in the presence of tyrosol at 50, 100 and 200 mmol l-1, during 48 h. Next, antimicrobial activity was assessed through metabolic activity (XTT reduction assay) and the number of colony-forming units (CFUs). Scanning electron microscopy observations were performed in order to analyse biofilm structure. Tyrosol, mainly at 200 mmol l-1, significantly decreased the metabolic activity and number of CFUs for all single and mixed-species biofilms formed on both surfaces. SEM images suggested cell damage caused by tyrosol. Conclusion: Tyrosol showed inhibitory effects against biofilms formed by important oral pathogens. Significance and Impact of the Study: This is the first study showing the antibiofilm effect of tyrosol on Candida species and Strep. mutans in single and mixed cultures. These results may be useful in the development of topical therapies focused on preventing biofilm-associated oral diseases, such as denture stomatitis and dental caries.
Keywords: Antimicrobials; Biofilms; Fungi; Quorum sensing; Streptococci